(untitled) (Research, Society and Development, 2022)
Introduction: Williams (1992) states that nutrition is an important tool within the practice of physical exercise. When oriented correctly, it can reduce fatigue, prolong the athlete’s training time or even improve the post-workout recovery process. Objective: It aims to analyze in articles, theses and books, found in academic websites, the characterization of the profile and the routine related to the use of dietary supplements in male individuals. Methodology: This work is a bibliographical research. Results> As a result, a significant use of dietary supplements was identified, mainly aimed at aesthetic gain (muscle mass), with the most consumed supplement corresponding to the one that is most easily acquired and consumed, due to its rapid absorption and effects. Results and discussions: In today’s globalized world, marked by the influence of the media in society, the number of people seeking research related to aesthetics has been growing exponentially. Therefore, in general, individuals with a high level of education and financial resources can pay for the practice of physical exercises and exercises related to healthy eating, most of the time they have information about nutrition and physical exercises. Conclusion: Through the above considerations, it is possible to state that to carry out a bibliographical research it is to follow non-random paths, since this type of research requires a high degree of epistemological vigilance, observation and care in choosing and forwarding the methodological procedures